Answers

  • Brainly User
2016-03-13T16:12:24+08:00
Equation A:  

     x + y = 39
     x = 39 - y

Equation B:

     y < 2x

Since x = 39-y (see Equation A), then:
 
     y < 2x
     y < 2 (39 - y)
     y < 78 - 2y
     y + 2y < 78
     3y < 78
     3y/3 < 78/3
     y < 26
     y = {25, 24, 23, ...}

Solve for x using the highest value of y; y = 25:
     
     x + y = 39
     x + 25 = 39
     x = 39 - 25
     x = 14

Solve for x using y=24:
     x + 24 = 39
     x = 39 - 24
     x = 15

If y = 23, x = 16.
If y = 22; x = 17.

Therefore x = {14, 15, 16, ...)

ANSWER:
The solution are:
x = {14, 15, 16, ...}        Interval notation: [14, ∞)
y = {25, 24, 23, ...)        Interval notation: (-∞, 26)
0